Traditional Theater Learning Based on the Revitalization of the Folklore of the Hanging Stone of Batak Toba Community - Irwansyah Irwansyah; Dilinar Adli; Rusell Akbar F (BIRCU, 2020)
The revitalization of the Batu Gantung Batak Toba tribe story in the Simalungun Regency Area, is a lesson that brings students closer to real life, which cannot be separated from their culture. This story is the origin of Lake Toba, which until now we can see, and is one of the cultural heritages used as a tourism object in North Sumatra. The revitalization of the Batu Gantung story becomes a process of transferring knowledge by positioning educators as facilitators in the teaching and learning process. This study will examine the folklore of the Batak Toba tribe which has meaning in the life system of the people who believe in supernatural powers. This study aims to develop a revitalization-based learning tool for the preservation of folklore. Development is rigged with a 4-D model namely define, design, develop and disseminate. The learning material developed is in the form of elements in image transfer, both in terms of stories, functions, patterns, and meanings, which become a show based on on the rules of society. This research uses a qualitative descriptive method, and The instruments used were observation, recording, interview, center study.